Evidence for a link between mortality in acute COPD and hospital type and resources. Issue 11 (29th October 2003) - Roberts, C M; Barnes, S; Lowe, D; Pearson, M G
Abstract : Background: The 1997 BTS/RCP national audit of acute care of chronic obstructive pulmonary disease (COPD) found wide variations in mortality between hospitals which were only partially explained by known audit indicators of outcome. It was hypothesised that some of the unexplained variation may result from differences in hospital type, organisation and resources. This pilot study examined the hypothesis as a factor to be included in a future national audit programme. Methods: Thirty hospitals in England and Wales were randomly selected by geographical region and hospital type (teaching, large district general hospital (DGH), small DGH). Data on process and outcome of care (death and length of stay) were collected retrospectively at 90 days on all prospectively identified COPD admissions over an 8 week period. Each centre completed a questionnaire relating to organisation and resources available for the care of COPD patients. Results: Eleven teaching hospitals, nine large DGHs, and 10 small DGHs provided data on 1274 cases. Mortality was high (14%) with wide variation between centres (IQR 9–19%). Small DGHs had a higher mortality (17.5%) than teaching hospitals (11.9%) and large DGHs (11.2%). When corrected for confounding factors, an excess of deaths in small DGHs was still observed (OR 1.56 (CI 1.04 to 2.35)) v teaching hospitals. Analysis of resource and organisational factors suggested higher mortality was associated with fewer doctors (OR 1.5) and with fewer patients being under the care of a specialist physician (OR 1.8). Small DGHs had fewest resources. Conclusion: Significant differences in mortality may exist between hospital types. The findings justify further study in a proposed national audit.